Моллюски рода Theodoxus (Gastropoda, Pectinibranchia, Neritidae) Азово-Черноморского бассейна - Анистратенко, О.Ю.; Старобогатов, Я.И.; Анистратенко, В.В. (Вестник зоологии, 1999)
Установлено, что в водоемах Азово-Черноморского бассейна ныне обитают 7 видов Theodoxus Montfoft, 1810 . Описан Theodoxus velox V. Anistratenko, sp. n. По фотоизображению 6 синтипов Nerita fluviatilis Linnaeus, 1758 (типового вида рода Theodoxus) выделен лектотип этого вида. Анализируется проблема таксономического значения окраски и рисунка на раковинах ТTheodoxus. Приведены иллюстрированные описания всех рецентных видов Theodoxus региона, даны определительная таблица, краткие сведения по их распространению и зоогеографической принадлежности. The genus Theodoxus Montfoft, 1810 is shown to be represented by 7 recent species in the basin of the Black and Azov Seas. Theodoxus velox V. Anistratenko, sp. n. is described. To clarify the concept of species, the lectotype of Nerita fluviatilis Linnaeus, 1758 is designated herein basing of a photograph of the 6 syntypes. Taxomic significance of the shell coloration and pattern in Theodoxus is discussed. Illustrated descriptions, brief data on distribution and zoogeography and the key to all the recent species of Theodoxus inhabiting the region of the Black and Azov Seas basin, are given.